Game Edukasi Untuk Anak TK Dan Dampak Penggunaan Android Di TK Bintang Timur P.Siantar - Dewi Yohana Br Ginting; Raheliya Br Ginting; Meiliyani Br Ginting; Asprina Br Surbakti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Community service activities are carried out at Bintang Timur Kindergarten in Pematang Siantar in order to help children at an early age understand android educational games that are suitable for consumption by the child himself. Educational games as a support for children's cognitive development so that parents must understand various types of educational game applications, how to choose the right educational games, and how to install on cellphones. The implementation method used is presentation, demonstration, practice, brainstorming, and sharing about educational games to the Principal at Bintang Timur Kindergarten, Pematang Siantar. This activity was carried out through three stages, namely 1) socialization, 2) mentoring, 3) monitoring and evaluation. The results of the implementation of this activity are: 1) understanding of android educational games as a support for children's cognitive development in the very good category. This is indicated by the percentage of indicators of achievement of recognizing educational games (96%), choosing educational games (89%), installing educational games (93%), and implementing educational games (86%); 2) obtained a positive response as seen from the attendance indicator of participants reaching 93% of the target and enthusiastic participants during the activity from the beginning to the end of the activity. The ultimate goal of introducing educational games is that parents are IT literate so that they are able to monitor their children in using cellphones, especially when playing games.